Systematic Product Development for Chili Paste in Ban Than-Om Community, Thung Tako District, Chumphon Province - Srewitoon, Charintorn; Kaewsom, Chatnalin; Sriphon, Thitima (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research aimed to study the principles and procedures of systematic product development and transfer knowledge on systematic product development to empower the community. The results were as follows: 1) In terms of management and raw materials, Ban Than-Om Community members purchased local raw materials; 2) In terms of production, the community had a clear and systematic production plan in packaging design and branding. The researchers, students, and community members had discussed and exchanged knowledge that led to the packaging and brand prototype; and 3) In terms of knowledge transfer, the researchers created a tool to survey the sample size of 300 people. It found that the consumers’ buying decision gave the highest score in all aspects. Buying frequency was mostly twice per week with a buying quantity of 200 grams per purchase. Buying channel was mostly from the local market for their own consumption. The most preferred choice for consumer buying decision was packaging size and carrying convenience and the most preferred product was sour chili paste. Based on the consumer survey results, Ban Than-Om Community members applied the information for product development and variation by including the production of sour chili paste. After a survey, the cooperation, unity, and exchange of knowledge occurred. Moreover, the community started to use cost and profit analysis system and official accounting. Product weight, quantity, and production time were also recorded with a better management system.